Pengembangan Aplikasi Front End Pembuatan Surat (E-Surat) Dinas Komunikasi, Informatika, dan Statistik Provinsi Bali - Rara Iswari, Ni Putu Ary; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
Dinas Komunikasi, Informatika dan Statistik Provinsi Bali is a Regional Organization which has the task of resolving the problems of Information Technology (IT) within the Bali Provincial Government and all regions in the Province of Bali. After a month of observing the field of Tata Kelola Pemerintahan Elektronik, the author found a problem in diskominfos namely manual archiving and uniformity of the format of the letter in which the format of the previously made letters still differed from each creation and sometimes writing errors. Based on this, an application for making letters (E-Surat) of the Office of Dinas Komunikasi, Informatika dan Statistik Provinsi Bali was developed. In this journal the author focuses on the front end which consists of design, animation and system validation. There are several features that have been successfully developed in this application, namely master data and the making of assignment letters (SPT) and official travel orders (SPPD). With the success of developing these features, it was concluded that the author was able to produce an analysis and development of the E-Surat application of Dinas Komunikasi, Informatika, dan Statistik Provinsi Bali which can help make mailing easily and quickly.